Histone lysine methyltransferase SUV39H1 is a potent target for epigenetic therapy of hepatocellular carcinoma. Issue 2 (30th May 2014) - Chiba, Tetsuhiro; Saito, Tomoko; Yuki, Kaori; Zen, Yoh; Koide, Shuhei; Kanogawa, Naoya; Motoyama, Tenyu; Ogasawara, Sadahisa; Suzuki, Eiichiro; Ooka, Yoshihiko; Tawada, Akinobu; Otsuka, Masayuki; et al.
<x xml:space="preserve">Abstract</x> Histone H3 lysine 9 trimethylation (H3K9me3) is associated with transcriptional repression and regulated by histone lysine methyltransferases such as SUV39H1 and ESET. However, the functional roles of these enzymes in hepatocellular carcinoma (HCC) remain uncertain. In this study, we conducted loss‐of‐function assays for HCC cells. SUV39H1 knockdown but not ESET knockdown reduced H3K9me3 levels and impaired HCC cell growth and sphere formation. The pharmacological inhibition of SUV39H1 by chaetocin resulted in cell growth inhibition and inducing cellular apoptosis in culture and xenograft subcutaneous tumors. Real‐time polymerase chain reaction analysis indicated high levels of SUV39H1 expression in 24 of 42 (57.1%) HCC surgical samples compared with corresponding nontumor tissues. Immunohistochemistry identified high levels of H3K9me3 and ESET proteins in 23 (54.8%) and 29 (69.0%) tumor tissues, respectively. However, these proteins' expressions were only observed in biliary epithelial cells and periportal hepatocytes of nontumor tissues. Expression levels of SUV39H1 but not those of ESET were significantly correlated with H3K9me3 levels. The cumulative HCC recurrence rate was significantly higher for patients with elevated SUV39H1 expression and H3K9me3 levels. In conclusion, our data indicate that elevated SUV39H1 expression and high levels of H3K9me3 have important roles in HCC development and progression. Therefore, the pharmacological inhibition of SUV39H1 may be a promising therapeutic approach for HCC treatment.